Efektivitas Penggunaan Media Teknologi Informasi dan Komunikasi berbasis Video Pembelajaran Interaktif dalam meningkatkan Hasil Belajar Pendidikan Agama Islam di SMPN 1 Ciruas dan MTsN 1 Kota Serang - Ayu Yulianti; Yuyun Rohmatul Uyuni; Rifyal Ahmad Lugowi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the effectiveness of using Information and Communication Technology (ICT)-based interactive learning videos in improving students’ achievement in Islamic Religious Education (PAI) at SMPN 1 Ciruas and MTsN 1 Kota Serang. The research employed a quantitative approach with a quasi-experimental method using the Nonequivalent Control Group Design. The participants consisted of 128 eighth-grade students who were purposively divided into two groups: the experimental class using interactive learning videos and the control class using conventional methods. Data were collected through learning achievement tests (pretest and posttest) and analyzed using non-parametric statistics, namely the Wilcoxon Signed-Rank Test and the Mann–Whitney U Test. The results revealed a significant improvement between pretest and posttest scores in both schools and in both groups. However, the improvement in the experimental class was greater than that in the control class. The Mann–Whitney U Test showed a significant difference at MTsN 1 Kota Serang (p < 0.001), whereas no statistically significant difference was found at SMPN 1 Ciruas (p > 0.05), although the experimental class tended to achieve higher results descriptively. These findings indicate that the use of ICT-based interactive learning videos is effective in enhancing Islamic Religious Education learning outcomes, with varying impacts depending on institutional context and student characteristics.